Causes of Exodontia in adult dentition and its association with Age in Tertiary Dental Practice - Lubna Yousaf, Meral Fatima, Muhammad Asif Shahzad, Ghulam Muhammad Paracha, Beena Kali (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To identify the causes of exodontia in adult dentition and its association with Age in Tertiary dental practice. Study design: Descriptive study Place and duration of study: Oral and Maxillofacial surgery department of Azra Naheed Dental College, a tertiary care dental setup in Raiwind, Lahore from Jan 2021 to June 2021. Methodology: Different engines like PubMed, Google Scholar, and Medline as well as other Oral Surgery journals were searched for relevant articles. This Study comprised of 400 patients selected by random sampling. The consent is taken from the patients before collecting their data. Only permanent teeth extracted for different causes are included in the study. Data was analysed using SPSS 24. Results: Among the 400 patient cases evaluated for exodontia, the chief cause for tooth extraction was because of grossly carious tooth 230 (57.50%), followed by Periodontal reasons 71 (17.75%). This study included patients whose age group range is from 11-69 years, with 62% males and 38% females. A notable difference was observed between cause of tooth extraction and different age groups. Conclusion: Emphasis on dental education can prevent the tooth loss. Common oral diseases such as dental caries at their various stages of progression and periodontal diseases should be highlighted by the oral health promotion campaigns. In addition, consistent dental check-ups at schools, colleges and workplaces should be made compulsory. In addition, the community field trips should be organized. By doing so an increase in oral health awareness may also intimidate patient’s perspective waiting until acute symptoms develop. As a follow-up to this study, it is recommended that a more representative sample of the general population be evaluated. Keywords: Exodontia, Non-Restorable, Caries